ACTR-42. THE USE OF ADVANCED DIFFUSION MRI PARAMETERS IN THE ASSESSMENT OF TREATMENT RESPONSE IN GLIOBLASTOMA USING MULTI-B VALUE ACQUISITION AND A HISTOGRAM-BASED APPROACH. (5th November 2018) - Islam, Shah; Morrison, Melanie; Grech-Sollars, Matthew; Orton, Matthew; Waldman, Adam
Abstract: PURPOSE: Imaging biomarkers to assess early treatment response in gliomas are important for guiding optimal clinical decision-making for individual patients, and as platforms for multi-institutional clinical trials of novel therapies. Current Response Assessment in Neuro-Oncology (RANO) criteria, rely on subjective, semi quantitative measurements with limited sensitivity and specificity in the early treatment phase. Previous diffusion imaging studies have indicated early sensitivity to treatment response, however optimum acquisition and analysis approaches have yet to be established. The purpose of this study is to assess the utility of advanced quantitative diffusion MRI derived from multi B-value acquisitions in the assessment of treatment response, using a spatially independent approach. METHODS: We used least-square fitting to model six diffusion parameters from mono-, bi-, and stretch-exponential models, and performed a histogram analysis of voxels located within ROIs defined by enhancing tumour and increased signal on FLAIR sequences. Histograms were generated for 10 patients with GBM at 3 time-points before, at 6 weeks, and 3 months treatment with standard-of-care regimen (RT with concomitant and adjuvant temozolomide). Changes in the histograms percentile profiles were evaluated across the various time-points, back-projected onto MRI images for spatial correspondence, and compared with RANO assessment from structural MRI at the latest timepoint. RESULTS, DISCUSSION & CONCLUSION: Percentile profiles changed over the course of therapy, reflecting known biological changes in the tumour microenvironment in response to radiotherapy and chemotherapy; these preliminary data suggest differential changes in diffusion parameters early in treatment. Spatially-independent diffusion parameter comparisons abrogate the confound of voxel misregistration due to tumour growth/shrinkage. Further assessment of this dataset, augmented by on-going patient recruitment across multiple centres, will provide insight to the prognostic value of advanced diffusion MRI as a standardized method for treatment response assessment.